Self leveling epoxy (SLE) topcoat color and TDS on lab room under contact no.: BRACU/New Campus/2022/482 (RFA-004) - Kansai Nerolac Paints (Bangladesh) Limited (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of only PDF version of drawings.